THE COMPARISON OF INCOME AND THE RISK FARMING OF CRYSTAL GUAVA FARMING OF PARTNERED AND NON-PARTNER FARMER WITH THE GOVERNMENT IN SEMARANG - Hasri Nurain; Wiludjeng Roessali; Edy Prasetyo (AGROLAND: The Agricultural Sciences Journal, 2019)
This study analyzed the income and factors that affect the crystal guava farming income at partnered and non-partnered farmers with the Agricultural Department of Semarang City Government The survey was done with the respondents that were chosen by purposively. A total of each 30 respondents were interviewed on partnered and non-partnered farmers. The data collected were analyzed by multiple linear regression test and coefficient variants. The result showed that there was a different revenue between partnered and non-partner farmers with the government. The income of partnered farmers was IDR 14,835,818.60/year, while the income of non-partnered farmers was IDR 75,717,383.27/year. The variables of the number of trees, the amount of production, cost farming, and the statues of farmers significantly affected the income of crystal guava farming. Meanwhile, the amount of NPK fertilizer and age were not significantly affected the income of crystal guava farming. The risk of farming of partnered farmers was higher than non-partner farmers.